WEB-BASED SHIP DATA COLLECTION INFORMATION SYSTEM AT THE PORT OF BENTENG SELAYAR - Ma'arief Al Imran, Abdul; Ramadhan, Rafi' (Jurnal Media Elektrik, 2025)
This research aims to design and test a web-based information system for ship data collection at the Port of Benteng Selayar. This system is expected to improve the performance of the staff of the Class III Port Management Unit of the Selayar Fortress and make it easier for the public, especially residents of the Selayar Islands Regency, to access ship schedule information at the port. This research uses Research and Development (R&D) methods to produce and test the effectiveness of the developed products. The results of the study show that this system is able to replace the manual method previously used in collecting ship data, reduce errors in making reports, and make it easier for the public to access ship schedules. The system test uses the ISO 25010 standard with eight test aspects, where the results show that the developed information system meets excellent quality standards, including aspects of functionality, reliability, performance efficiency, usability, portability, security, compatibility, and maintenance. The system has been tested using WAPT, GTMetrix, and Quttera software, and tested on a variety of different devices and browsers. Based on the results of the trial, this information system is suitable for use by port managers and the community.